Retour vers le futur : le commerce d’échange international au cours des années 80 - Cooper, Andrew (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1989)
Barter has been commonly portrayed as a dangerous element in international relations. Barter is portrayed in much of the literature as a cyclical phenomenon which flourishes with economic depression and fades away with prosperity. It is also said by many critics that barter should be considered a destructive economic practice. Finally, great emphasis is placed on the geopolitical importance of barter. In particular, barter is associated with the aggressive economic statecraft practiced by Nazi Germany in the 1930s.This article attempts to look more closely at the assumptions of the critics of modem barter. The author concludes that there are fundamental differences between the 1930s and the 1980s. Barter in the 1980s appears not to point towards a destructive past but a dynamic and complex future.